Effect of sintering temperature on structural and dielectric properties of Bi and Li co-substituted barium titanate ceramic. Issue 14 (1st November 2016) - Alkathy, Mahamoud S.; Gayam, Rahul; Raju, K.C. James
Abstract: Bi and Li co-substituted barium titanate, Ba0.98 (Bi, Li)0.02 TiO3 ceramic samples were sintered at different temperatures using conventional solid state sintering technique. X-Ray Diffraction patterns confirm tetragonal phase in all the sintered samples. Microstructure analysis using Scanning Electron Microscopy (SEM) reveals increasing grain sizes with an increase in sintering temperature. Dielectric spectroscopy performed in the range of 40 Hz to 2 MHz at room temperature shows that the dielectric constant increases with increasing sintering temperature, reaching a maximum of value of 1200 at 40 Hz where the dielectric loss observed was less than 0.02 for samples sintered at 1300 °C. Temperature dependant impedance spectroscopy data in the range of 30–300 °C was used to measure AC conductivity. The activation energy of grains was deduced through Arrhenius plots. Loss tangent at different frequencies for 1300 °C sintered samples was less than 0.1 over the entire temperature range. The high dielectric constant with a low dielectric loss at elevated temperatures make Ba0.98 (Bi, Li)0.02 TiO3 samples suitable for Multi-Layer Ceramic Capacitors (MLCC)s used in high-temperature applications.